2015
DOI: 10.1055/s-0035-1555138
|View full text |Cite
|
Sign up to set email alerts
|

Use of Flow-Through Anterolateral Thigh Perforator Flaps in Reconstruction of Complex Extremity Defects

Abstract: Our experience showed that the flow-through ALTP flap is reliable and suitable for reconstruction of complex defects of the extremities, as well as for various other clinical purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
0
33
0
5
Order By: Relevance
“…Our previous experience showed that a flow-through technique is required to revascularize the additional flap (Qing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous experience showed that a flow-through technique is required to revascularize the additional flap (Qing et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A segment of vastus lateralis muscle was included as the muscle flap to obliterate the dead space. The surgical technique used to harvest the additional perforator flap was similar to our previous study (Qing et al, ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…12,13 Moreover, flow-through flaps allow future microsurgical intervention and multistage flap procedures without increased risk of vascular compromise of the extremity in case of recurring disease. 14 Even though the latissimus dorsi muscle flap and the anterolateral thigh flap are mostly described for the flow-through procedure, this technique is applicable in many other flaps 7,8,[15][16][17][18][19][20][21][22][23][24][25][26] with the only requirement being the presence of a side branch with an acceptable diameter for the anastomosis to the distal stump of the recipient artery.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In some selected cases, an arterial and venous defect can be reconstructed by means of a "flow-through" microsurgical flap, or by the use of a venous loop for the creation of a temporary arteriovenous fistula. 4,5 The purpose of this study was to retrospectively evaluate the need for venous and arterial reconstruction and its results in a clinical series of free microsurgical transfers for lower limb reconstruction, operated at two reconstructive surgery centers: the University of Palermo (Italy) and the University of Gent (Belgium).…”
mentioning
confidence: 99%